Comparative study on microleakage degree of five kinds of fluid resins under different temperature conditions - GUO Xinxin, JING Xue, MA Siyu, ZHAO Sha, LI Tao (Editorial Office of Stomatology, 2024)
Objective To study the effect of temperature on microleakage of Beautifil Flow Plus F00, FiltekTM Z350 XT, SDR, Tetric®N-Flow and Constic, and to provide reference for clinical selection of ideal fluid resins. Methods A total of 60 adult detached premolars removed for orthodontic extraction were divided into 10 groups(n=12), which were divided into F00A group, Z350A group, SDRA group, TetricA group and ConsticA group according to whether they had undergone cold and hot cycle aging test, and F00B group, Z350B group, SDRB group, TetricB group, ConsticB group, a total of 10 groups. The occlusal surface of each isolated tooth was prepared into a type Ⅰ hole with the width of 2 mm, length of 4 mm and depth of 2 mm, which was filled with the corresponding fluid resin respectively. Methylene blue staining experiment was performed on specimens in group A, and methylene blue staining experiment was performed on specimens in group B after 5 000 times of cold and hot cycling aging experiment. The crowns of all specimens were dissected longitudinally along the long axis of the tooth body from the direction of buccal tongue(palate). The degree of microleakage in each group was observed under stereomicroscope, and the data were recorded and analyzed statistically. Results ①There was no significant difference in the degree of microleakage between the F00A group, the Z350A group, the SDRA group, the TetricA group and the ConsticA group(P>0.05). ②The degree of microleakage in the SDRB group and TetricB group was significantly higher than that in the F00B group and Z350B group(P<0.05). ③Temperature had a significant effect on the microleakage degree of Beautifil Flow Plus F00, FiltekTM Z350 XT, SDR, Tetric® N-Flow and Constic(P<0.05). Conclusion ①There was no significant difference in the degree of immediate microleakage of Beautifil Flow Plus F00, FiltekTM Z350 XT, SDR, Tetric® N-Flow, and Constic without cold and hot cycle aging experiments. ②After the cold and hot cycle aging experiments, the microleakage degree of SDR fluid resin and Tetric® N-Flow fluid resin was high, and the edge tightness was poor. Beautifil Flow Plus F00 fluid resin and FiltekTM Z350 XT fluid resin had a low degree of microleakage and better edge tightness. ③The micro-leakage degree of Beautifil Flow Plus F00, FiltekTM Z350 XT, SDR, Tetric® N-Flow and Constic was aggravated by the cold and hot cycle aging experiments.